(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study determines the extent information and communication technology (ICT) skills possessed by office technology and management graduateworkers in the civil service of Enugu State. Two research questions guided the study and four null hypotheses were tested. Descriptive survey design was adopted for the study. The population was 200 Office Technology and Management (OTM) graduate workers from 27 ministries in Enugu State. No sampling was taken since the population size was manageable.A five point rating scale questionnaire containing 22 items in two clusters was used for data collection. The instrument was validated by three expertone in measurement and evaluation and two inbusiness education from the Faculty of Education, Nnamdi Azikiwe University, Awka. The reliability of the instrument was ascertained using test-retest whichyielded co-efficient values of 0.61 and 0.90for clusters B1 and B2with an overall reliability co-efficient value of 0.76.Mean and standard deviation were used to answer the research questions and determine the homogeneity of the respondents while t-test was used to test the null hypothesesat 0.05 level of significance. The findings revealed that the subjects lowly possessed internet service skills and moderately possessed file management skills. There was a significant difference in the mean ratings of male and female respondents on possessed internet service skill but no significant difference on possessed file management skills. Based on the findings, the researcher concluded thatOTM graduate workers cannot perform effectively adequately without possessing relevant ICT skills. It was recommended among others that government ministries should procure the latest model of ICT facilities to increase their usage by workers for enhanced efficiency, effectiveness and productivity.